Student-Centered Pedagogical Practices and Perceived Graduate Employment Readiness in Selected Chinese Public Universities: The Mediating Role of Career Decision Self-Efficacy - Liya Ma; Izazol Binti Idris (Journal of Advances in Humanities Research, 2026)
Guided by a selective application of Social Cognitive Career Theory (SCCT), this study examined the relationships among student-centered pedagogical practices (SCPP), career decision self-efficacy (CDSE), and perceived graduate employment readiness (GER) among final-year undergraduate students at five selected public universities in China. A quantitative cross-sectional design was employed, and data from 589 students were analyzed using partial least squares structural equation modeling (PLS-SEM) with SmartPLS 4.0. The results showed that SCPP was positively associated with CDSE (β = 0.45, p < 0.001) and GER (β = 0.22, p < 0.001), while CDSE was positively associated with GER (β = 0.41, p < 0.001). The indirect association between SCPP and GER through CDSE was also significant (β = 0.18, p < 0.001). The model explained 39.8% of the variance in perceived GER. The study applies, rather than extends, a focused SCCT-consistent pathway linking perceived educational experiences, CDSE, and perceived GER. The results suggest that universities may align student-centered learning with career-development activities intended to support students' career-related confidence and perceived readiness for the university-to-work transition.